A Taxonomic Study of the Genus Eurema Hübner, [1819] (Lepidoptera: Pieridae) in Thailand - JERATTHITIKUL, EKGACHAI; LEWVANICH, ANGOON; BUTCHER, BUNTIKA AREEKUL; LEKPRAYOON, CHARIYA (Tropical Natural History, 2009)
The taxonomic study of the genus Eurema Hübner, [1819] from museum specimens over Thailand is reported. Seven hundred and one imagoes (butterflies) were examined, resulting in ten distinct species and some 15 species-subspecies being recorded. These were comprised of two species from the subgenus Eurema (E. brigitta and E. laeta) and eight species from the subgenus Terias (E. ada, E. andersoni, E. sari, E. nicevillei, E. novapallida, E. blanda, E. simulatrix and E. hecabe). A dichotomous key to the species of the genus in Thailand, based on the wing marking patterns with illustrations and descriptions of the male genitalia where this aids identification, is presented. The distribution of the genus in Thailand, and the taxonomic problems with wing marking variations of E. hecabe hecabe are discussed.